The intelligent control system for the technical radio beacons condition of the navigation and landing complex - D. D. Gabrielyan; P. I. Kostenko; O. A. Safaryаn (Научный вестник МГТУ ГА)
The article considers the possibility of developing control systems for the technical condition of radio beacons (RB) transmitting channels generators for the airport navigation and landing complex using artificial intelligence systems (AIS). The feature of using AIS to develop the technical control system is integrating a multidimensional likelihood function into the knowledge base. By means of merely measurements of signal phases generated in RB, the given function makes it possible to evaluate:– average frequencies of generated signals in RB;– deviations of average frequencies from the required values throughout the entire observation interval;– random deviations of the current frequency values from the average ones at each measurement interval;– relative frequency instabilities of each of generators.The results obtained and their variation over the time allow us to carry out:– monitoring the technical condition of RB channels generators;– diagnostics of the technical condition of RB channels generators;– forecasting the technical condition of RB channels generators and making a decision concerning the status of the controlled generators according to the CORRECT OPERATION-DETERIORATION-FAILURE criterion.